IBM Edukasi Manajemen Laktasi Untuk Menyukseskan Program ASI Eksklusif Pada Ibu Menyusui - Yuni Astuti; Tuti Anggarawati; Erni Suprapti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Lactation management is an effort to help mothers achieve success in breastfeeding. This effort takes place from the pregnancy period, delivery, and the breastfeeding period until the child is 2 (two) years old. The practice of breastfeeding can also be carried out by breastfeeding from various backgrounds. However, not all mothers have the full time and opportunity to breastfeed their babies directly, including worker. Increased knowledge is needed to strengthen awareness in increasing knowledge and behavior in lactation management and exclusive breastfeeding. One of the efforts made is the transfer of knowledge regarding lactation management and exclusive breastfeeding. The result of this activity is that there is an increase in understanding about lactation management and exclusive breastfeeding after education.